2015
DOI: 10.5468/ogs.2015.58.6.530
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally high level of CA-19-9 in a benign ovarian cyst

Abstract: CA-19-9 antigen is mainly elevated in cases of gastrointestinal tract malignancy, including of the pancreas, colorectum, and biliary tract. CA 19-9 antigen can also be elevated in ovarian mucinous neoplasms, however, as well as in many benign conditions. Markedly raised levels of more than 10,000 U/mL were almost observed in advanced stage of malignancy. We report herein the case of a 37-year-old woman who presented with an abnormally high level of CA 19-9 antigen associated with benign mucinous cystadenoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 9 publications
0
20
0
1
Order By: Relevance
“…Altered glycosylations in cancer provide potential targets for therapy [ 21 , 61 , 62 ], but despite numerous developed anti-glycan antibodies [ 63 , 64 , 65 , 66 ], most are not compatible with clinical applications. SLe a is a potential therapeutic target in many types of cancers [ 28 , 29 ], including pancreatic and colorectal cancers [ 59 , 67 , 68 ]. Here, we demonstrate a platform for optimizing functional therapeutic antibodies against cancer glycans, exemplified by targeting SLe a .…”
Section: Discussionmentioning
confidence: 99%
“…Altered glycosylations in cancer provide potential targets for therapy [ 21 , 61 , 62 ], but despite numerous developed anti-glycan antibodies [ 63 , 64 , 65 , 66 ], most are not compatible with clinical applications. SLe a is a potential therapeutic target in many types of cancers [ 28 , 29 ], including pancreatic and colorectal cancers [ 59 , 67 , 68 ]. Here, we demonstrate a platform for optimizing functional therapeutic antibodies against cancer glycans, exemplified by targeting SLe a .…”
Section: Discussionmentioning
confidence: 99%
“…We present this case in order to build on the growing body of evidence suggesting that CA 19-9 levels are useful in the diagnosis and management of MCT [7,10]. Cases of ovarian neoplasms such as ovarian clear-cell and endometrioid carcinomas [11] with increased CA 19-9 levels, and benign neoplasms with increased CA 19-9 have been documented in the literature previously [3][4][5]. Pyeon et al [5] reported a case of a benign ovarian cyst with CA 19-9 levels of 2,753 U/mL that then returned to normal postoperatively [5].…”
Section: Discussionmentioning
confidence: 99%
“…Cases of ovarian neoplasms such as ovarian clear-cell and endometrioid carcinomas [11] with increased CA 19-9 levels, and benign neoplasms with increased CA 19-9 have been documented in the literature previously [3][4][5]. Pyeon et al [5] reported a case of a benign ovarian cyst with CA 19-9 levels of 2,753 U/mL that then returned to normal postoperatively [5]. Similarly, Sampaio et al [4] reported an MCT in a 50-year-old woman with the second highest reported level of CA 19-9 (8922.75 U/mL) [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations